2005
DOI: 10.1007/s00330-005-0031-2
|View full text |Cite
|
Sign up to set email alerts
|

T1 and T2 relaxivity of intracellular and extracellular USPIO at 1.5T and 3T clinical MR scanning

Abstract: In this study we evaluated the effects of intracellular compartmentalization of the ultrasmall superparamagnetic iron oxide (USPIO) ferumoxtran-10 on its proton T1 and T2 relaxivities at 1.5 and 3T. Monocytes were labeled with ferumoxtran-10 by simple incubation. Decreasing quantities of ferumoxtran-10-labeled cells (2.5x10(7)-0.3x10(7) cells/ml) and decreasing concentrations of free ferumoxtran-10 (without cells) in Ficoll solution were evaluated with 1.5 and 3T clinical magnetic resonance (MR) scanners. Puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 33 publications
14
138
2
1
Order By: Relevance
“…The relatively large nanoparticles, which have a size on the order of plasma proteins, initially distribute in the blood pool, where they cause strong T1 and T2 relaxation time enhancement (37). The nanoparticles subsequently slowly extravasate across the sinusoids of microvessels in RES organs and accumulate in the interstitium, where they are slowly phagocytosed by macrophages.…”
Section: Molecular Imaging: Mr Imaging Monitoring Of Macrophage Migramentioning
confidence: 99%
“…The relatively large nanoparticles, which have a size on the order of plasma proteins, initially distribute in the blood pool, where they cause strong T1 and T2 relaxation time enhancement (37). The nanoparticles subsequently slowly extravasate across the sinusoids of microvessels in RES organs and accumulate in the interstitium, where they are slowly phagocytosed by macrophages.…”
Section: Molecular Imaging: Mr Imaging Monitoring Of Macrophage Migramentioning
confidence: 99%
“…In this experimental setup, diffusion of ferumoxtran-10 within the solution is unrestricted. It has been shown that r 1 and r 2 relaxivities of ferumoxtran-10 freely dispersed in solution are stronger compared to when the contrast agent is compartmentalized in cells (26). This needs to be considered especially when applying the results of the current study to imaging of intracellularly compartmentalized USPIOs.…”
Section: Discussionmentioning
confidence: 89%
“…The T2* effect is affected by the magnetic field strength, and according to the report by Simon et al (21), the T2 relaxivity of USPIO has been demonstrated to be stronger at 3.0 T as compared to 1.5 T. Therefore, a different SI change of USPIO-enhanced MRI between 1.5 T and 3.0 T could be expected, which might result in a different diagnostic accuracy of lymph node metastasis detection. Even though there was no significant difference of the SI ratio for malignant lymph nodes, we found significance of the SI ratio for benign lymph nodes.…”
Section: Discussionmentioning
confidence: 97%